Dampak Perkembangan Teknologi Informasi dan Komunikasi terhadap Perilaku dan Kesehatan Remaja - Alsri Windra Doni; Aprizal Ponda; Darwel (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
The impact of advancements in Information and Communication Technology (ICT) on students' behavior and health has become a serious issue. Excessive use of mobile devices, social media, and the internet has altered how students interact, learn, and spend their leisure time, triggering sleep disorders, digital addiction, social isolation, and decreased physical activity. This initiative aims to enhance teenagers' understanding of the effects of ICT on their health and behavior. The method involves educational sessions using videos and books, followed by a post-test to assess whether there is an improvement in students' knowledge and understanding of the effects of ICT on their behavior and health, as well as to evaluate the success of this community service program. The activity was conducted at SMA Muhammadiyah on June 4, 2024, with 36 students. The results showed that 91.7% of students understood the importance of responsible gadget use. However, 75% of students experienced negative effects such as sleep disturbances and decreased concentration, while 66.67% reported headaches due to excessive gadget use, often caused by poor posture and neck strain. Conclusion :This initiative successfully raised students' awareness of the impact of technology, emphasizing the importance of using gadgets wisely.